THE IMPACT OF MERIDONAL WIND TO THE MOISTURE TRANSPORT AND WEATHER FORMATION IN WEST INDONESIA ON FEBRUARY 2014 - Mahardiani Putri Naulia Batubara (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2017)
Wind is the movement of air masses due to the physical differences between continent and ocean. In that motion, wind will transfer the moisture, momentum, and also flux that will affect to the weather formation in the region that will be passed. Meridional wind is a wind with vertical movement from north to the south and vice versa. Meanwhile, moisture transport is the total of water vapor which is transfered by one air mass volume in a different range. The availability of water vapor is one of the main components in the formation of convective clouds in producing rain. In February 2014, weather anomaly occurred in western Indonesia, where the rainfall declined drastically and it became so dry in a wet month. In a comparison to its climatology, the weather condition that formed in February 2014, is the first time occurred in western Indonesia. Geographycally, in the northern of west Indonesia is bordered primarly to Asia continent and South China Sea, so that in monsoon period or cold surge period that usually happened on December, January, and February, the cold air masses willl be transfered to west Indonesia. For that reason, this paper will discuss about the availability of water vapor in February 2014 and the amount of moisture transport. The data that will be used in this observation is data from the European Centre for Medium-Range Weather Forecast (ECMWF) with resolution 0,1250 x 0,1250 and will be processed by the Grid Analysis and Display System (GrADS) application.Keywords: Meridional wind, moisture transport, rainfall